O tamanho populacional das cidades importa? Uma análise econômico-financeira dos municípios do COREDE Fronteira Noroeste do Rio Grande do Sul - Argemiro Luís Brum; Daniel Knebel Baggio; Maurício Galeazzi Medeiros de Farias (Confins)
The main objective of this article is to identify, based on the theme of emancipations-development, if the process of division of the municipalities is a relevant factor for the development of the regions. A reflection is made on the fiscal and financial situation of the emancipated territories, which generally results in small municipalities, taking as a reference those who make up the COREDE Fronteira Noroeste. For this research, data from official bodies, census and economic indicators were used to assist in the analysis, interpretation and characterization of the difference between the municipalities in the chosen region. It is concluded that a large part of the emancipations ends up generating small municipalities with a small population, a weak tax base and a decrease in the amount of services provided. As a consequence, these small municipalities end up depending, almost exclusively, on transfers from the central government. Thus, it would be pointless to create new municipalities in the interior of the country, with some exceptions.